Evaluation of the performance of three meat rabbit breeds recently introduced to Egypt: 1. Litter weight and related traits - Yamani K.A.O.; El Maghawry A.M.; Soliman A.M.; Farghaly H.M.; Tawfeek M.I. (Rabbit production in hot climates, 1994)
Data on 3571 parturitions produced by 94 Californian (Cal), 311 New Zealand White (NZW) and 384 Bauscat (Bos) purebred doe rabbits (paternal half-sisters) during two successive years of production (1991/92 and 1992/93), were used in the present study. The present work aimed to evaluate litter traits of the three breeds recently introduced (1991) to Egypt and the adaptation of three strains in the new environment in San El-Hagar, Shrkiya Governorate, Egypt.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)